A look at comets - Spangenburg, Ray, 1939- (Out of this world (Franklin Watts, Inc.), 2003)
A comprehensive look at comets, from man's earliest observations of "hairy stars," to recent sightings of Comet Shoemaker-Levy 9 and Halle-Bopp, to future space missions to study comets in the outer solar system.